Determinants of Job Satisfaction amongst Medical Officers of Primary Health Centre in Anand District, Gujarat, India - Deepak B Sharma; Utkarsh M Shah; Rakesh Patel; Vidushi Gupta; Uday Shankar Singh (Journal of Clinical and Diagnostic Research, 2018)
Introduction: Dissatisfaction with job is invariably linked with decreased work performance. Discontent provider is more likely to face difficulty in caring for his patients and provide quality medical care. Thus, provider dissatisfaction results in patient dissatisfaction which deleteriously affects health outcomes. Aim: The study was undertaken with the objective of finding determinants of job satisfaction amongst Primary Health Centre (PHC) doctors in Anand, Gujarat, India. Materials and Methods: The present cross-sectional analytical study was conducted amongst 50 PHC Medical Officers (MO), MBBS and Ayurveda, Yoga and Naturopathy, Unani, Siddha, Homeopathy (AYUSH) of Anand, Gujarat, India. Self-administered questionnaire method was used to obtain the responses from the participants. Job satisfaction was seen in four different heads/dimensions like “Workload”, “Relationships with Staff”, “Personal Difficulties” and “Availability of Infrastructure”. Some questions were in Likert scale and some questions were of dichotomous type. All the individual heads were summated to get a final score. Total scores ranged from 6-36. Categorical analysis of all the individual variables was also done. Face validity and consensual validity, and content validity of the questionnaire was checked. The data entry was done in excel and analysed using SPSS version 15.0. Qualitative as well as quantitative analysis was done. Mann-Whitney U test, and chisquare test were applied and values were calculated. Fisher’s exact test was also applied. Results: Out of total 50 MO, 33 (66.0%) were MBBS doctors and the rest were BAMS and BHMS doctors. Overall job satisfaction score was found to be significantly different amongst two groups (p=0.037). The two groups (MBBS and AYUSH) were statistically different in the workload scores (p=0.008). Conclusion: Overall job satisfaction scores were poor amongst PHC doctors. It was observed that doctors were unsatisfied on account of facilities in terms of good infrastructure, support services, good human relations, and personal conflicts. If we want sustainable development at primary healthcare level, job satisfaction is must, as doctors are providers of health services and they must be satisfied so that they can provide best of the services to a large number of rural beneficiaries.